Relationship Between Stress And Mental Health - khairuman, khairuman (Public Health Journal, 2024)
Siblings of individuals with neurodevelopmental conditions (NDCs) are a minority population at higher genetic and environmental risk of poorer neurocognitive and psychosocial outcomes compared to siblings of individuals without NDCs. Depressive symptoms were detected in almost one in five older adults. High perceived stress is associated with psychological and academic difficulties among college students. Student status was significantly associated with higher levels of perceived stress in almost all life domains.